PROSES PEMBENTUKAN DATA ARKEOLOGI BAWAH AIR KAPAL LIBERTY DI TULAMBEN - Henki Riko Pratama (BRIN, 2018)
Abstract USAT Liberty Shipwreck is one of the underwater archaeological remains that attracts a considerable number of underwater tourism enthusiasts both locally and internationally. Despite of its popularity, the historical background of the Liberty Shipwreck remains unrevealed as well as its deposition process. This article aims to discuss the process of archaeological data formation on the wrecksite of Liberty Ships in Tulamben Waters along with the causing factors that affecting its current condition. This research used qualitative methods with inductive reasoning to explain the process of archaeological formation data. The results of this research indicate that there are two main factors affecting the process of the shipwreck formation which are; the behavioral process and the transformation process. The behavioral process occurs when the ship was still in its cultural system until it was deposited on the seafloor, this consisted of several stages: procurement, manufacture, use, abandonment and decay. Once deposited in the waters of Tulamben Beach, the Liberty Ship was affected by C-transform and N-transform factors. The main C-transform factors were the looting and diving activities, while N-transform factor consisted of the eruption of Mount Agung, the dynamics of Tulamben seashore and the process that occur under the waters.